1969
DOI: 10.1037/h0027140
|View full text |Cite
|
Sign up to set email alerts
|

Item length, acoustic similarity, and natural language mediation as variables in short-term memory.

Abstract: Four experiments on short-term retention are reported. Retention is known to be an inverse function of number of elements in the item, and Exp. I inquired if this finding is a function of the ease with which natural language mediators (NLMs) are formed. Acoustic similarity and item length were variables in Exp. I. The NLMs functioned as hypothesized, but a confounding with associative strength precluded a theoretical decision about the number-of-elements variable. The effects of acoustic similarity were essent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

1971
1971
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 19 publications
1
12
0
Order By: Relevance
“…Experiment I was sensitive enough only to detect the increase in auditory-and-visual confusion errors (which would tend to occur no matter which of the preceding strategies the subject was using). Evidence indicating use of an auditory store is sometimes found in this paradigm (Shankweiler, Liberman, Mark, Fowler, & Fisher, 1979) and sometimes not (Adams, Thorsheim, & McIntyre, 1969).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Experiment I was sensitive enough only to detect the increase in auditory-and-visual confusion errors (which would tend to occur no matter which of the preceding strategies the subject was using). Evidence indicating use of an auditory store is sometimes found in this paradigm (Shankweiler, Liberman, Mark, Fowler, & Fisher, 1979) and sometimes not (Adams, Thorsheim, & McIntyre, 1969).…”
Section: Resultsmentioning
confidence: 99%
“…It has been noted several times that immediate ordered recall is better for a simultaneous visual presentation than for a sequential visual presentation (Crowder, 1966;Mackworth, 1962;Marcer, 1967). Two reasons for this have been suggested: (1) Having all the stimuli available at the same time provides more opportunity for organizing the stimuli into meaningful chunks (Adams et al, 1969;Marcer, 1967); and (2) the subject can allot attention to the stimuli in the most advantageous fashion (Crowder, 1966). These two factors probably playa role in increasing recall of a simultaneous presentation, but neither would explain why a simultaneous presentation produces more visual confusion errors and fewer auditory confusion errors than a sequential presentation.…”
Section: Resultsmentioning
confidence: 99%
“…Depending on whether list words and distractors are preferentially encoded phonologically or semantically, phonological or semantic similarity should play the dominant role. Previous research has shown that immediate serial recall of verbal material rests predominantly on phonological memory traces, but that with filled delays of several seconds, phonological similarity effects tend to decline and semantic features become more important (Adams, Thorsheim, & McIntyre, 1969;Baddeley & Ecob, 1970). The complex span paradigm involves filled delays following each memory item; therefore, it could be that at the time of recall, semantic representations predominate over phonological ones.…”
Section: Overview Of Experimentsmentioning
confidence: 99%
“…Predictable sequences that conform to S's language habits will be encoded more easily and into fewer chunks, and are hence more likely to be recalled (Miller, 1956). While such coding will be simplest with predictable material, recent failures to observe acoustic similarity effects (Adams, Thorsheim, & Mcintire, 1969;Laverty & Turvey, 1970) suggest that it may also occur with consonant sequences, given appropriate conditions. Such results certainly indicate that Ss are not coding in terms of letter names; they do not, however, mean that Psychon.…”
mentioning
confidence: 99%
“…Furthermore, all the letters in each sequence were presented simultaneously. a procedure that recent work suggests may minimize acoustic confusability effects (Adams, Thorsheim, & McIntire, 1969;Laverty & Turvey, 1970). The following experiment, therefore, uses the teclmique that seems most likely to favor acoustic coding, sequential auditory presentation, and studies the relationship between acoustic confusability, predictability, and probability of recall of letter sequences of varying approximation to English.…”
mentioning
confidence: 99%